Aid and Trade - A Donor's Perspective - Felicitas Nowak-Lehmann Nowak-Lehmann D.; Inmaculada Martínez Zarzoso; Stephan Klasen; Dierk Herzer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
One reason donors provide foreign aid is to support their exports to aid-recipient countries. Time series data for Germany suggests an average return of between US 1.04 to US 1.50 for each US dollar of aid spent by Germany. Although this is well below previous estimates, the value is robust to different specifications and econometric approaches. Interestingly, we find strong evidence of crowding out between bilateral donors in the sense that bilateral aid from other EU members significantly reduces exports from Germany to the recipients. The evidence suggests that, in the long-run, aid causes exports and not vice versa. We discuss the implications these findings might have for aid volumes and allocation.
Keywords: F10; F35; C23; 330; trade; foreign aid; donors; time series based panel estimation techniques